Nurturing a Literary Revival: The ISTAID Center's Endeavors in Harnessing Islamic Thought and Information for Da'wah in Medan City, North Sumatra (1993-2022) - M Yakub; Ahmad Sampurna; Farah Sabir Mohammed (Khazanah Sosial, 2023)
ISTAID Center is an institution active in the fields of da'wah, education, and thought. The ISTAID movement adheres to the principle of literacy based on the Islamic worldview and the ta'dib pattern as its main foundation. This research employs a historical research approach encompassing heuristics, verification, interpretation, and historiography. The findings of this study reveal that ISTAID focuses on promoting literacy in mosques. Mosques are chosen due to their significant role as centers for social and religious activities and their potential in da'wah and literacy efforts. ISTAID spreads newsletters using accessible language that is easily understood by the community. In conclusion, the current presence of ISTAID Center in fostering literacy among the people of Medan City has proven to be highly effective. Through the consistent efforts of the ISTAID movement, the dissemination of Islam can be improved. This research offers a deeper understanding of the development of Islamic literacy through ISTAID Center, with a specific emphasis on the advancement of literacy civilization within mosques.